2001
DOI: 10.1097/00007632-200103150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Fenestration of the Extracranial Vertebral Artery

Abstract: Fenestration of the extracranial course of the vertebral artery is a developmental or congenital anomaly. A review of the literature demonstrated that this is apparently only a coincidental finding and has no pathologic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 7 publications
0
44
0
1
Order By: Relevance
“…Fenestration differs from duplication in that the artery has a single origin and then separates into two parallel arteries along the length of its course [1]. Fenestrations of the extracranial course of the vertebral arteries are rare and are usually noted incidentally during angiographic studies or post mortem examinations [2]. Some authors have suggested that fenestration of vertebral arteries is a congenital abnormality without pathological significance [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenestration differs from duplication in that the artery has a single origin and then separates into two parallel arteries along the length of its course [1]. Fenestrations of the extracranial course of the vertebral arteries are rare and are usually noted incidentally during angiographic studies or post mortem examinations [2]. Some authors have suggested that fenestration of vertebral arteries is a congenital abnormality without pathological significance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Fenestrations of the extracranial course of the vertebral arteries are rare and are usually noted incidentally during angiographic studies or post mortem examinations [2]. Some authors have suggested that fenestration of vertebral arteries is a congenital abnormality without pathological significance [2]. Arterial dissection and thromboembolism can arise within fenestrated vessels, and shearing forces induced by vigorous head movement may be responsible [3].…”
Section: Introductionmentioning
confidence: 99%
“…9 Sim et al described that sometimes there occurs failure of the controlled regression of this portion of the primitive dorsal aorta along with the two inter segmental arteries which leads to the double origin and duplication of the vertebral arteries. 10 The bilateral occurrence of these failures is the reason behind the bilateral duplication of the vertebral arteries. The vertebral vessels are responsible for the formation of the transverse foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The variation of the basilar artery dilation and fenestration is common. Sim et al [4] pointed out that this kind of variation was only random, non-symptomatic, was not clinically relevant. However, Miyazaki et al [5] believed that there might be some correlation between the basilar artery fenestration with multiple intracranial aneurysms.…”
Section: Commentarymentioning
confidence: 99%